EFFECT OF ALLERGEN-SPECIFIC IMMUNOTHERAPY COURSES ON COGNITIVE ACTIVITY IN CHILDREN WITH POLLINOSIS - O. I. Muradova; L. S. Namazova-Baranova; G. A. Karkashadze; O. I. Maslova; R. M. Torshkhoeva; A. Y. Tomilova; A. A. Alexeeva; T. V. Turti; E. A. Vishnyova; T. A. Konstantinidi (Педиатрическая фармакология)
Relevance. Allergic pathology, particularly, pollinosis, may reduce cognitive functions in children. Objective: study effect of allergen-specific immunotherapy on cognitive functions in children with pollinosis and relation of cognitive functions dynamics to repeated ASIT courses. Patients and methods. We determined condition of cognitive functions in 97 children of 8‑17 years of age with pollinosis in comparison with their healthy peers using a psychophysiological computer complex “Psychomath”. Results. We revealed reduction in cognitive activity parameters in most children with pollinosis during remission. Concurrent persisting allergic rhinitis aggravated reducing in cognitive functions parameters. Conclusion. We confirmed positive effect of allergen-specific immunotherapy: cognitive functions improve significantly in children with pollinosis; the effect becomes more pronounced after repeated courses.